Efeitos do antimoniato de n-metilglucamina e sbv sobre parâmetros citotóxicos, genotóxicos e mutagênicos em cultura de leucócitos humanos - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Leishmaniasis is an infectious disease that can affect the skin, mucosa and internal organs. Although affecting about 1.5 million people each year, leishmaniasis has few therapeutic alternatives. N-methylglucamine antimoniate (Sb-GAM) is the drug of choice to treat leishmaniasis according to the World Health Organization. The treatment with this drug can induce the individual to a frame of toxicity, since it is derived from the antimony (Sb), a metal free found in the earth's crust, principally in the form trivalent and pentavalent oxidation. The trivalent form has clastogenic and carcinogenic potential both in vitro and in vivo. However, there are few genotoxic studies involving Sb-GAM. The main contribution of this study was to evaluate in vitro the cytotoxic, genotoxic and mutagenic parameters of five different concentrations (5, 10, 20, 40 and 50 μg/mL) of Sb-GAM and SbV in human leukocyte. For the cytotoxicity and genotoxicity tests we apply statistical one-way analysis of variance (ANOVA) and for mutagenicity tests the two-way ANOVA. Among the multiple comparisons we used the Tukey test and consider a statistically significant result when p <0.05. Cell proliferation, chromosomal instability, the alkaline comet assay and double- stranded DNA breaks assays, showed that both forms of Sb were genotoxic when compared to the negative control, at least, in one of the concentrations tested. Cell viability and micronucleus tests were used to evaluate, respectively, cytotoxicity and the mutagenicity. Additionally, there was assessed the number of apoptotic and necrotic cells, as well as nuclear division cytotoxicity index. All these parameters showed significant changes. In an unprecedented strategy, the intracellular Sb level was quantified and correlated with the different exposure concentrations and, from this, we could induce that the Sb inflow occurs in a concentration-dependent, but with a zero-order kinetics. Altogether, our results show clearly that Sb-GAM has cytotoxic, genotoxic and mutagenic effects on human leukocytes at the concentrations tested.
Efects of n-metilglucamine antimoniate and sbv on citotoxic, genotoxic and mutagenic parameters in human culture leukocite
Keywords: Leishmaniose; Antimoniato de meglumina; Genética toxicológica; Mutagenicidade; Citotoxicidade; Saúde pública; Farmacovigilância; Leishmaniasis; Meglumine antimoniate; Genetic toxicology; Mutagenicity; Cytotoxicity; Public health; Farmacovigilance